The Tradition of Celebrating the Birthday of Prophet Muhammad Reception of Wetu Telu Adherents in Bayan Village, North Lombok Regency, Regarding Mahabbah in Surah Ali Imran, Verse 31 - Kusumawardana, Muhammad Ardi; Tyas, Baiq Ayu Darma Ning (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Wetu Telu is a belief system and religious practice still observed by some Sasak Muslims in Lombok, West Nusa Tenggara. The purpose of this study is to identify the forms of practice and understanding related to the acceptance of mahabbah among Wetu Telu adherents and to explore the arguments supporting this acceptance. The research questions addressed in this study include: What is the general meaning of mahabbah in the Qur'an? How do Wetu Telu Muslims in Bayan Village celebrate the birthday of the Prophet Muhammad (Prophet's Birthday)? What are the patterns of acceptance and the goals of Wetu Telu adherents in interpreting mahabbah based on Surah Ali 'Imran, verse 31? This study employs a qualitative descriptive method. The qualitative approach involves gathering information in a natural setting using scientific methods. Meanwhile, the descriptive method seeks to describe a specific object or historical event, followed by an effort to draw general conclusions based on historical facts-one of which is conducted through interviews. The findings of this study indicate that the reception of mahabbah among Wetu Telu adherents, as reflected in Surah Ali 'Imran verse 31, manifests in a different form of love compared to mainstream Muslims in its application. Wetu Telu adherents integrate local cultural traditions and perform rituals in their religious activities. In applying the theoretical framework of this study, the encoding process refers to Sunan Prapen, who introduced the Qur'an to Wetu Telu followers through Sufi mystical teachings. As a result, cultural syncretism remains prevalent among its adherents today. Meanwhile, the decoding or reception pattern of mahabbah varies: a small portion of adherents accept the meaning of the Qur'anic text in its entirety, known as hegemonic dominance, while the majority contextualise the text, a process referred to as negotiation